2015
DOI: 10.1186/s12916-015-0453-x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of three or one breathing technique training sessions for breathlessness in people with malignant lung disease

Abstract: BackgroundAbout 90 % of patients with intra-thoracic malignancy experience breathlessness. Breathing training is helpful, but it is unknown whether repeated sessions are needed. The present study aims to test whether three sessions are better than one for breathlessness in this population.MethodsThis is a multi-centre randomised controlled non-blinded parallel arm trial. Participants were allocated to three sessions or single (1:2 ratio) using central computer-generated block randomisation by an independent Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 33 publications
(39 reference statements)
2
88
0
Order By: Relevance
“…Patients with cancer diagnoses were the next studied population of focus (n=13), [38][39][40][41][42][43][44][45][46][47][48][49][50] followed by patients with interstitial lung disease (n=8), [51][52][53][54][55][56][57][58] and lastly one study focussed on patients with Huntington's disease (Table 1) Page S35…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with cancer diagnoses were the next studied population of focus (n=13), [38][39][40][41][42][43][44][45][46][47][48][49][50] followed by patients with interstitial lung disease (n=8), [51][52][53][54][55][56][57][58] and lastly one study focussed on patients with Huntington's disease (Table 1) Page S35…”
Section: Resultsmentioning
confidence: 99%
“…Even simpler interventions may assist patients with intrathoracic cancer. 46 The teaching of breathing management techniques were delivered over a one-hour long session or over three one-hour long sessions. In terms of the primary outcome, patient reported intensity of worst-breathlessness over the past 24 hours was the same in both groups.…”
Section: Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Complex interventions using a similar approach to PR, but tailored to people of poorer performance status, have been developed, piloted, and tested in trials which include people with lung cancer [13][14][15][16][17][18][19]. Three adequately powered randomized controlled trials (RCTs) [15,17,18] confirmed benefit in terms of reduced breathlessness intensity [15], reduced distress due to breathlessness [17], and improved mastery over breathlessness [18].…”
Section: Treating Breathlessness In Lung Cancer Patients: the Potentimentioning
confidence: 99%
“…However, although the burden of cancer treatments is recognized at this stage, we must not assume that supportive care carries none. An adequately powered RCT demonstrated that, for patients with lung cancer, a single hour's session of breathing training was of equal benefit (worst breathlessness over the past 24 hours) to the standard three sessions at weekly intervals, and patients receiving three sessions experienced worse distress due to their breathlessness [19]. The authors suggested that this could be because the burden of visits to clinic, or even home visits from clinic staff, outweighed the benefits of additional sessions.…”
Section: Treating Breathlessness In Lung Cancer Patients: the Potentimentioning
confidence: 99%